Suppression of inflammation and fibrosis using soluble epoxide hydrolase inhibitors enhances cardiac stem cell‐based therapy. (13th August 2020) - Sirish, Padmini; Thai, Phung N.; Lee, Jeong Han; Yang, Jun; Zhang, Xiao‐Dong; Ren, Lu; Li, Ning; Timofeyev, Valeriy; Lee, Kin Sing Stephen; Nader, Carol E.; Rowland, Douglas J.; Yechikov, Sergey; et al.
Abstract: Stem cell replacement offers a great potential for cardiac regenerative therapy. However, one of the critical barriers to stem cell therapy is a significant loss of transplanted stem cells from ischemia and inflammation in the host environment. Here, we tested the hypothesis that inhibition of the soluble epoxide hydrolase (sEH) enzyme using sEH inhibitors (sEHIs) to decrease inflammation and fibrosis in the host myocardium may increase the survival of the transplanted human induced pluripotent stem cell derived‐cardiomyocytes (hiPSC‐CMs) in a murine postmyocardial infarction model. A specific sEHI (1‐trifluoromethoxyphenyl‐3‐(1‐propionylpiperidine‐4‐yl)urea [TPPU]) and CRISPR/Cas9 gene editing were used to test the hypothesis. TPPU results in a significant increase in the retention of transplanted cells compared with cell treatment alone. The increase in the retention of hiPSC‐CMs translates into an improvement in the fractional shortening and a decrease in adverse remodeling. Mechanistically, we demonstrate a significant decrease in oxidative stress and apoptosis not only in transplanted hiPSC‐CMs but also in the host environment. CRISPR/Cas9‐mediated gene silencing of the sEH enzyme reduces cleaved caspase‐3 in hiPSC‐CMs challenged with angiotensin II, suggesting that knockdown of the sEH enzyme protects the hiPSC‐CMs from undergoing apoptosis. Our findings demonstrate that suppression of inflammation and fibrosis using an sEHI represents a promising adjuvant to cardiac stem cell‐based therapy. Very little is known regarding the role of this class of compounds in stem cell‐based therapy. There is consequently an enormous opportunity to uncover a potentially powerful class of compounds, which may be used effectively in the clinical setting. Abstract : Stem cell replacement offers a great potential for cardiac regenerative therapy. However, one of the critical barriers to stem cell therapy is a significant loss of transplanted stem cells from ischemia and inflammation in the host environment. Here, we demonstrate that inhibition of the soluble epoxide hydrolase (sEH) enzyme to decrease inflammation and fibrosis in the host myocardium increases the survival of the transplanted human induced pluripotent stem cell derived‐cardiomyocytes (hiPSC‐CMs) in a murine postmyocardial infarction model.